The process approach to the teaching of writing in Malaysian secondary schools in Sarawak : theory and practice - Chung, Huey Ching (Universiti Malaysia Sarawak, (UNIMAS), 1997)
The English Language teaching profession of Malaysia is continually searching actively for pedagogical innovations which will improve the teaching of English as ESLIEFL for its secondary school students throughout the country. One recent `revolutionary' innovation, process writing, has brought. about many controversial issues among the ESL/EFL teachers in Sarawak, as they sort through their own ideologies and visions of the teaching-learning process. The present study attempts to investigate the (a) response of teachers and (b) the barriers behind the hesitancy of many teachers to use the process writing approach to teach writing in schools. Results indicated that there is a tapestry of factors determining the nonfeasibility of the process writing approach in the teaching of writing. Student attitudes towards the language and learning, are interwoven tightly with classtime, teacher-workloads, competing teacher-priorities and differing teacher. ideologies regarding student-language competence and performance, as well as the success of language learning. The major recommendation of this study is the importance of flexibility. Teachers should "marry" different teaching strategies with process writing to suit the needs and language ability of the students and the competing priorities for teachers' dass-time.